THE IMPACT OF FRAMING EFFECT: HOW FRAMING EFFECT AFFECTS STUDENTS IN CHOOSING UNIVERSITY’S MAJOR - Suroyo Suroyo; Bima Maulana Putra (Jurnal Analisa Sosiologi, 2022)
Many students in choosing higher education majors are not in accordance with their abilities and interests. This will have an impact on students in making decisions on the choice of majors.  This research is qualitative survey study with all students of the University of Riau as the population in this study, with 556 samples covering eight departments and three faculties using representative sampling technique with criteria for early students (semester 1 and semester 3). The results of the study prove that in terms of practicality and knowledge possessed by students to choose majors, such as motivation, excelling, enjoyable, easeness, preference will affect decision making (thinking process, and ambiguity). The decision to choose a major that is not in accordance with the major can have a negative effect on the student. This is something that students should pay attention to. Keywords: Decision-Making, Framing Effect, Major, Students AbstrakBanyak mahasiswa dalam memilih jurusan pendidikan tinggi tidak sesuai dengan kemampuan dan minatnya. Hal ini akan berdampak pada mahasiswa dalam mengambil keputusan pada pemilihan jurusan. Penelitian ini merupakan study qualitative berjenis survey dengan mahasiswa Universitas Riau sebagai populasi dalam penelitian ini, dengan 556 sampel yang meliputi delapan jurusan dan tiga fakultas dengan menggunakan teknik representative sampling dengan kriteria mahasiswa awal (semester 1 dan semester 3). Hasil penelitian membuktikan bahwa dalam hal praktis dan pengetahuan yang dimiliki oleh mahasiswa untuk memilih jurusan, seperti motivasi, exelling, enjoyable, easiness, preference akan berpengaruh terhadap pengambilan keputusan (proses berpikir, dan ambiguitas). Keputusan dalam memilih jurusan yang tidak sesuai dengan jurusan dapat memberikan efek negatif pada mahasiswa tersebut. hal ini yang harus menjadi perhatian oleh mahasiswa.   Kata kunci: Framing Effect, Mahasiswa, Jurusan, Pengambilan Keputusan